2021
DOI: 10.1051/0004-6361/202040168
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of theGaia–VLBI position differences being related to radio source structure

Abstract: Context. We report the relationship between the Gaia–VLBI position differences and the magnitudes of source structure effects in VLBI observations. Aims. Because the Gaia–VLBI position differences are statistically significant for a considerable number of common sources, we discuss and attempt to explain these position differences based on VLBI observations and available source images at centimeter wavelengths. Methods. Based on the derived closure amplitude root mean square (CARMS), which quantifies the magni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Two sources (1538+149 and 2353+816) presenting particularly large X-to-O offsets are also ICRF3 defining sources. In several sources (0119+115, 0346+800, 0749+540, 0859+470, 1157−215, 1652+398, 1742−078, and 2223−052), the optical centroid is close to a radio jet feature (a particularity also recently supported by Xu et al 2021), suggesting that in such sources the optical emission is dominated by optically thin jet features in the downstream region of the jet. Such regions of synchrotron emission are expected to have a more organized magnetic field and higher linear polarization (e.g., Ginzburg 1979), which is supported by observations in radio Lister & Homan (2005) and optical Kovalev et al (2020).…”
Section: Analysis and Resultsmentioning
confidence: 54%
“…Two sources (1538+149 and 2353+816) presenting particularly large X-to-O offsets are also ICRF3 defining sources. In several sources (0119+115, 0346+800, 0749+540, 0859+470, 1157−215, 1652+398, 1742−078, and 2223−052), the optical centroid is close to a radio jet feature (a particularity also recently supported by Xu et al 2021), suggesting that in such sources the optical emission is dominated by optically thin jet features in the downstream region of the jet. Such regions of synchrotron emission are expected to have a more organized magnetic field and higher linear polarization (e.g., Ginzburg 1979), which is supported by observations in radio Lister & Homan (2005) and optical Kovalev et al (2020).…”
Section: Analysis and Resultsmentioning
confidence: 54%
“…VLBI-Gaia offsets are a widely discussed topic (e.g. Kovalev, Petrov & Plavin 2017;Xu et al 2021, and references therein) and it has been shown that such offsets can be used as a tool to distinguish between the accretion disc and jet emission regions (Plavin, Kovalev & Petrov 2019). Six sources from our sample have coordinates within 0.5 arcsec from optical sources in the Gaia EDR 3 (Gaia Collaboration 2021).…”
Section: Smile L9mentioning
confidence: 99%
“…However, we found a lack of connection (correlation coefficient smaller than +0.1 with a p-value of about 0.4). Since the CARMS was supposed to be correlated with the structure index (Xu et al 2019) and Xu et al (2021) reported the existence of a connection between the Gaia-VLBI and the CARMS, it is surprising that the correlation tests lead to different results. We have no explanation yet in this regard and leave it for a future investigation.…”
Section: Cause Of Optical-to-radio Distancementioning
confidence: 99%